Subabool (Leucaena leucocephala) (Lam) Based Alley Cropping System in Semi-arid Sub-tropics of India - Meena, L. R. (Indian Forester, 2011)
Subabool [Leucaena leucocephala (lam) Dewit] play an important role in agroforestry system, which provides a way to sustain agricultural production under rising land pressure and worsening soil degradation conditions. It has unique properties and suitable for growing as hedgerows with other crops. It also carries important functions of a traditional bush fallow for nntrient recycling, source of green manure, firewood and staking material. Addition of Leuceanae pruned material increases total soil nitrogen and organic carbon. But consistent and considerable reduction in yield of associated field crops upto a level of 30-90 % was observed when sown as sole and mixed in alley cropping system but these losses of yield can be compensated by an additional yield obtained from Leucaena biomass. This reduction in yield of crops is due to hedgerow species in alley cropping competition with companion crops for available light, water and nutrients. Besides, Subabool supplies a good quality of feed to all kinds of animals because it contains high amount of protein, has good palatability and ability to withstand repeated defoliation. Moreover, its fodder is particularly useful for goats in the tropics as they can degrade to a great extent, even toxic amino acid (mimosine) present in Leucaena plant can be utilized by goats with out any adverse effect. The fodder available from this tree can also be fed to cow, camel, buffalo and sheep to limited extent because continuous feeding to animals may cause metabolic disorder.